Pengaruh Protokol Kesehatan dan Penerapan E-Ticketing terhadap Kepuasan Penumpang Kereta Api Sumatera Barat pada Masa New Normal - Marlenni, Loly; Frinaldi, Aldri (Policy, Law and Political Research Center, 2023)
The research purposes to examine the effect of health protocols and the implementation of e-ticketing on passenger satisfaction in West Sumatra train service during the new normal.This study uses an associative quantitative method. The data was collected through a survey questionnaire via google fromand quantitative data were got using a scale of Likert that had been tried for validity and reliability. Where the writer studied there was a population of 97 respondents, the sample obtained in this study was 56 respondents using the Slovin formula although a rate of error of 5% and the analysis in the research used multiple linear regression tests. The results showed that both health protocols and e-ticketing have a effect in significant and positive on passenger satisfaction. The findings suggest that the implementation of strict health protocols and efficient e-ticketing system is crucial in ensuring passenger satisfaction in the train service during the new normal. The study provides valuable insights for the railway industry in improving their services to meet the needs and passengers expectations in the current pandemic situation.